2006
DOI: 10.1103/physrevlett.96.140402
|View full text |Cite
|
Sign up to set email alerts
|

Pair Production and Optical Lasers

Abstract: Electron-positron pair creation in a standing wave is explored using a parameter-free quantum kinetic equation. Field strengths and frequencies corresponding to modern optical lasers induce a material polarization of the QED vacuum, which may be characterized as a plasma of e+e- quasiparticle pairs with a density of approximately 10(20) cm-3. The plasma vanishes almost completely when the laser field is zero, leaving a very small residual pair density n(r) which is the true manifestation of vacuum decay. The a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
109
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(116 citation statements)
references
References 32 publications
3
109
0
4
Order By: Relevance
“…Of particular interest are effects related to wave propagation in these plasmas, such as proposed pulsar radio emission processes (Luo et al, 2002), bulk acceleration of relativistic jets (Iwamoto and Takahara, 2002), jet formation (Sawyer, 2008;Wardle et al, 1998), electron-positron pair annihilation into one photon in the presence of a strong magnetic field (Harding, 1986), and also in laboratory environments, in problems such as pair production by optical lasers (Blaschke et al, 2006;Chen et al, 2011).…”
Section: Muñoz Et Al: Large-amplitude Waves In Relativistic Plasmasmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest are effects related to wave propagation in these plasmas, such as proposed pulsar radio emission processes (Luo et al, 2002), bulk acceleration of relativistic jets (Iwamoto and Takahara, 2002), jet formation (Sawyer, 2008;Wardle et al, 1998), electron-positron pair annihilation into one photon in the presence of a strong magnetic field (Harding, 1986), and also in laboratory environments, in problems such as pair production by optical lasers (Blaschke et al, 2006;Chen et al, 2011).…”
Section: Muñoz Et Al: Large-amplitude Waves In Relativistic Plasmasmentioning
confidence: 99%
“…White and Lightman, 1989), models of the early universe (Gibbons et al, 1985;Tajima and Taniuti, 1990;Tatsuno et al, 2003;Lesch and Pohl, 1992), supernova remnants and active galactic nuclei (Hardy and Thoma, 2000;Reynolds et al, 1996), pulsar magnetospheres (Curtis, 1991;Istomin and Sobyanin, 2007;Manchester and Taylor, 1977;Sturrock, 1971), magnetars (neutron stars with magnetic fields up to ∼ 10 14 G) (Beskin et al, 1993), hypothetical quark stars (Usov, 1998), and gamma-ray bursts (Piran, 1999(Piran, , 2004. Regarding laboratory plasmas, they have been considered in the study of ultra-intense lasers (Blaschke et al, 2006), and in laboratory and tokamak plasmas (Zank and Greaves, 1995). For instance, recent experiments on relativistic electron-positron creation with short ultra-intense laser pulses (∼ 10 20 W cm −2 ) have been performed (Chen et al, 2009), where measurements indicate the positron density to be ∼ 10 16 cm −3 .…”
mentioning
confidence: 99%
“…More recent theoretical investigations have shown that there is a second mechanism to create pairs. Even if the field strength is below E c , pairs can be created if the external field varies rapidly in time, as is characteristic of a laser pulse [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Such fields model the focus of counter propagating laser pulses in which the magnetic field components cancel. They have been used to investigate pair production for oscillating fields [33][34][35], pulsed fields [36,37] and pulsed fields with sub-cycle structure [38][39][40].…”
Section: Longitudinal and Transverse Fieldsmentioning
confidence: 99%